2017
DOI: 10.1016/j.actbio.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Thermally triggered hydrogel injection into bovine intervertebral disc tissue explants induces differentiation of mesenchymal stem cells and restores mechanical function

Abstract: Low back pain (LBP) is associated with degeneration of the intervertebral disc (IVD). We have previously described development of a jelly delivery system (hydrogel). This has the potential to deliver adult stem cells to the centre of the IVD, known as the nucleus pulposus (NP). Here, we have demonstrated that adult stem cells can be safely injected into the NP using small bore needles, reducing damage to the disc. Following injection the hydrogel integrates with surrounding NP tissue, promotes differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 61 publications
1
58
0
Order By: Relevance
“…A number of studies have documented positive results with MSCs in disc repair [37,49,65,182,183,184,185,186,187] and this has also been the subject of a number of definitive reviews [26,58,188,189,190,191]. The results we obtained with MSCs in the ovine annular lesion model of experimental DD are therefore consistent with these earlier findings.…”
Section: Discussionsupporting
confidence: 90%
“…A number of studies have documented positive results with MSCs in disc repair [37,49,65,182,183,184,185,186,187] and this has also been the subject of a number of definitive reviews [26,58,188,189,190,191]. The results we obtained with MSCs in the ovine annular lesion model of experimental DD are therefore consistent with these earlier findings.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, in vivo studies have reported that MSCs implantation into degenerated IVD leads to the regeneration of the NP. In a bovine IVD degeneration model, Thorpe et al [2017] found that by transplanting human bone marrow-derived (BM)-MSCs, the accumulation of ECM in NP could resume, thereby providing a combined cellular and mechanical repair. In another study, Marfia et al [2014] investigated the survival and implant efficacy of human adipose-derived (AD)-MSCs in a mouse IVD degeneration model.…”
mentioning
confidence: 99%
“…These systems are particularly useful as human tissue obtained from surgery can be utilized as small pieces of intact tissue and can be maintained in culture. Such systems have been employed to excellent effect to study proof of principle studies on regenerative approaches including biological, cellular, and injectable hydrogel systems . These studies can provide useful initial data on local tissue responses, integration and delivery to tissues, which are essential in the pathway to clinic.…”
Section: Bench Side Testing: In Vitro and Ex Vivo Testingmentioning
confidence: 99%